Pergeseran Paradigma Tentang Mesias Dalam Markus 1:40-45 - Victor Drajad Setiawan (Media (Jurnal Filsafat dan Teologi), 2021)
The main purpose of this paper is to discuss the way Jesus revealed His messianic identity in Mark 1:40-45. With the narrative analysis method, the author wants to show the shift in the meaning of the text from its historical context to the meaning that can be understood by today's readers. He recognized himself as the Messiah. However, he tried to keep his messianic secret until his resurrection. Jesus had a distinctive way of introducing His messianic identity. He chose not to publish his work or deliver teachings that were often not easy to understand. His resurrection was a turning point for the disciples in understanding His messianic status. When the Jewish Christian community spoke of the incomprehensible work of Jesus, they made their own meaning. They thought that this was Jesus' way of shifting the paradigm of the Messiah in the concept of thought of the Israelites at that time.